2021
DOI: 10.1149/1945-7111/ac2ec0
|View full text |Cite
|
Sign up to set email alerts
|

FeCoNiS Nanoparticles Integrated with Nitrogen−Doped Vertically Oriented Graphene via Single−Step Electrodeposition: An Efficient Bifunctional Catalyst for Overall Water Splitting

Abstract: The development of transition metal electrocatalysts to replace precious metal electrocatalysts is essential for the development of sustainable water splitting technology for the mass production of clean hydrogen. FeCoNiS/NVG (N-doped vertically oriented graphene) is fabricated via single-step electrodeposition. Benefiting from the vertical structure of FeCoNiS/NVG and intrinsic catalytic activity of FeCoNiS, FeCoNiS/NVG displays excellent catalytic activities toward the hydrogen evolution reaction (HER) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
2
1
0
Order By: Relevance
“…Our research group has prepared N-doped vertically oriented graphene by electrodeposition, integrated FeCoNiS on the substrate, and successfully prepared FeCoNiS/N-VG. [31] At a current density of 10 mA cm À 2 , compared with FeCoNiS/ VG (159 mV) and CoNiS/NVG (157 mV), the HER polarization curve of FeCoNiS/N-VG shows the lowest overpotential (126 mV), which is consistent with the OER results. The results showed that there is a strong interaction between FeCoNiS and N-VG, and the HER activity of quaternary metal chalcogenides is better than that of ternary and binary metal chalcogenides, which is due to the strong electron interaction between Fe, Ni, Co, and S.…”
Section: Doping Strategysupporting
confidence: 78%
See 1 more Smart Citation
“…Our research group has prepared N-doped vertically oriented graphene by electrodeposition, integrated FeCoNiS on the substrate, and successfully prepared FeCoNiS/N-VG. [31] At a current density of 10 mA cm À 2 , compared with FeCoNiS/ VG (159 mV) and CoNiS/NVG (157 mV), the HER polarization curve of FeCoNiS/N-VG shows the lowest overpotential (126 mV), which is consistent with the OER results. The results showed that there is a strong interaction between FeCoNiS and N-VG, and the HER activity of quaternary metal chalcogenides is better than that of ternary and binary metal chalcogenides, which is due to the strong electron interaction between Fe, Ni, Co, and S.…”
Section: Doping Strategysupporting
confidence: 78%
“…In addition to introducing non‐metals into the active material, this strategy can also be adopted on the conductive substrates, which often leads to a synergistic effect between the two substances, thus enhancing their electrolysis of water ability. Our research group has prepared N‐doped vertically oriented graphene by electrodeposition, integrated FeCoNiS on the substrate, and successfully prepared FeCoNiS/N‐VG [31] . At a current density of 10 mA cm −2 , compared with FeCoNiS/VG (159 mV) and CoNiS/NVG (157 mV), the HER polarization curve of FeCoNiS/N‐VG shows the lowest overpotential (126 mV), which is consistent with the OER results.…”
Section: Iron‐group Metal Chalcogenidessupporting
confidence: 78%
“…Hydrogen has become a potential substitute for fossil fuels due to its high combustion calorific value and no strict requirements on production sites. [1][2][3] Hydrogen production by electrolysis of water is the only way to produce hydrogen without pollution to the environment. [4][5][6] The kinetic process of water splitting is slowly, especially the oxygen evolution reaction (OER) involving the 4e − transfer process, so catalysts are required to increase the reaction rate and reduce the energy loss during water electrolysis.…”
mentioning
confidence: 99%